Oxidation of Primary Alcohols to Carboxylic Acids A Guide to Current Common Practice - Tojo, Gabriel; Fernandez, Marcos I. (Basic Reactions in Organic Synthesis, 2007)
This book, the second in the series Basic Reactions in Organic Synthesis, is a laboratory guide for the transformation of primary alcohols into carboxylic acids. It contains copious information on important experimental details and procedures for the successful and reliable completion of this oxidation. This work is an important addition to any laboratory involved in the preparation of organic molecules.